(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current effort entails the production and characterization of one schiff base compound, which includes the following: (3Z,3Z) -3,3’ -((oxybis(4,1-phenylene))biss(azanylylidene))biss(oxybis(4,1- phenylene))bis(oxybis(4,1-phenylene))bis(oxybis(4,1-phenylene))bis (indolin-2-one) The novel compounds were created by ligand interactions with Co+2, Ni+2, and Cu+2 are transitional positive metal ions.. To describe the formula of these elemental composition analysis, ligands and related compounds (C.H.N), infrared (IR) spectra, 1H-NMR spectroscopy , mass spectra were utilized. The ligand complexes identified as octahedral structure, with the ligand coordinating with metals through Oxygen and Nitrogen atoms